Role of immigrants on polish labour market - Grabowska, M. (My University, 2015)
In the nineties of the twentieth century, political, economical and social system changed in many countries. Restrictive controls of crossing border were removed. The East- Central European region became very diverse economically. The events freed a vast migration potential in the centre of Europe, also in Poland. Migration movements began to play a significant role in this country. At the beginning, emigra-tion dominated in Poland. The difference of wages and life conditions between Poland and destination countries was the reason for which many people left their places of origin. Another factor pushing Polish countrymen abroad in search of work was the increase in demand for work of foreigners in destination countries. Thus, a shortage was created on Polish domestic labour market which someone had to fill. That meant it was necessary to open Poland to immigrants. Immigration to Poland is an inevitable phenomenon; it is also beneficial for the country, for example because of the adverse demographic trends
Keywords: immigration; labour market; immigrants; mobility; illegal migrants; іммігранти; імміграція; ринок праці; мобільність; нелегальні мігранти